AGRICULTURAL LAND ON BUILT-UP HOUSING LOTS AND THE INCOMES OF COMMUNES: AN EXAMPLE OF ROKIETNICA COMMUNE IN THE POZNAŃ AGGLOMERATION - Maćkiewicz, Barbara; Karalus-Wiatr, Cecylia (Quaestiones Geographicae, 2017)
The strong connection between urbanisation processes and the transformation of farmland into built-up areas – mostly residential – has already been tackled in the literature. Still, in Poland this process of farmland loss, generally thought to be irreversible, occurs in a specific, often irrational and not fully registered way. What is more, this development is favoured by legislation, especially rules controlling the exclusion of land from agricultural production and real-estate taxation. Among the many detrimental consequences of those regulations are incomes of communes lower than they should be. The problem tackled in the article is that of the exclusion from agricultural use of only fragments of geodetic lots on which building investments are going on. The cost of the exclusion and the difference in the rates of the agricultural tax and the real-estate tax very often result in the exclusion of only a part of a lot, while the rest of it is formally still in agricultural use, even though its owner does not conduct any agricultural activity there. In this case two taxes have to be paid from one lot: the real-estate tax, on the land taken out of agricultural use and the building erected on it, and another, the agricultural tax, on land that is still a piece of farmland. This situation, especially in areas undergoing rapid urban sprawl, is common in Poland and has unfavourable consequences for the incomes of communes. It also leads to a discrepancy between data from the real-estate cadastre and the actual area of land in agricultural use, which greatly hampers an exact measurement and control of the real losses of land performing the agricultural function, including that with high-quality soils. The conducted research demonstrated that in 2014 nearly 7% (927) of all geodetic lots in Rokietnica commune, situated in the immediate neighbourhood of Poznań, were builtup housing lots, mostly carrying detached single-family houses, with fragments of farmland. Almost a half (49.4%) of the total area of those lots, 42 ha, was still agricultural land in the real-estate cadastre and subject to taxation not by the real-estate tax, but the much lower agricultural tax. Because of this difference in the two taxes, the annual receipts of the commune budget are 186,601 zlotys (43,395 euro) lower. It also turned out that more than 50% of farmland on those lots (21.8 ha) was arable land of the good land-capability class III, which is high for the conditions in the Poznań agglomeration. This not only corroborates the findings of earlier studies highlighting significant losses of good-quality arable land taking place as a result of urban sprawl, but it also means that in the Polish conditions actual losses are much higher than would follow from records in the real-estate cadastre. It can also be stated that the Polish legal rules not only fail to adequately protect farmland situated within metropolitan areas, but even favour its excessive loss.